SKEMA MODEL BISNIS SOSIAL UNTUK PENINGKATAN PRODUKTIVITAS PENGUSAHA TEMPE MIKRO DI PEDESAAN - Kusmulyono, Muhammad Setiawan; Salim, Agus; Wiraguna, Arfan; Khafidzi, Ahmad Tohari (STIE AMA Salatiga, 2025)
ABSTRACT : Tempeh is a multi-nutrient national food product that can be a solution to national food insecurity. Tempeh has advantages over other protein sources because it is affordable, easy to obtain, easy to process, and available in markets and even local vegetable vendors. Unfortunately, micro-scale tempeh entrepreneurs in rural areas are vulnerable due to fluctuations in imported soybean prices. Based on this, through a qualitative approach, this study seeks to explore the role of social entrepreneurship to be able to present a social business model scheme that can help tempeh entrepreneurs in rural areas. Social entrepreneurship is an appropriate concept to help tempeh because it provides a solution to social problems with entrepreneurial solutions. Three social business model schemes are presented to be proposed business assistance for tempeh, starting from the entrepreneur support model, market intermediary model, and employment-partnership model. This model can be an effective solution while maintaining local, traditional culture in tempeh production, but with more calculated risks and growing scale to ensure tempeh becomes a solution to national food insecurity. ABSTRAK : Tempe merupakan produk pangan nasional multi nutrisi yang mampu menjadi solusi kerawanan pangan nasional. Tempe memiliki keunggulan dari sumber protein lain karena harga terjangkau, mudah didapat, mudah diolah, dan tersedia di pasar hingga pedagang sayur lokal. Sayangnya, pengusaha tempe skala mikro di pedesaan memiliki kerentanan karena fluktuasi harga kedelai impor. Atas dasar itu, melalui pendekatan kualitatif, studi ini berupaya mengeksplorasi peran kewirausahaan sosial untuk dapat menghadirkan skema model bisnis sosial yang dapat membantu pengusaha tempe di pedesaan. Kewirausahaan sosial merupakan konsep yang tepat untuk membantu tempe karena menjadi solusi bagi masalah sosial dengan penyelesaian yang bersifat entrepreneurial. Tiga skema model bisnis sosial dihadirkan untuk menjadi usulan pendampingan bisnis bagi tempe mulai dari entrepreneur support model, market intermediary model, dan employment – partnership model. Model ini dapat menjadi solusi efektif dengan tetap menjaga budaya lokal, tradisional, dalam memproduksi tempe, namun dengan risiko yang lebih terkalkulasi dan skala yang semakin bertumbuh untuk memastikan tempe menjadi solusi atas kerawanan pangan nasional.